Does Sacrifice Avert Violence? Reflections from Nepal and the People’s War - Marie Lecomte-Tilouine (Antropologia, 2013)
The article explores the complex relationship between sacrificial rituals and violence within socio-political contexts. Drawing on extensive ethnographic research in Nepal, the study examines how Maoist revolutionary movements infused with sacrificial symbolism generated a unique form of revolutionary violence. The article delves into the paradoxical roles of sacrifice as both a regulator and a progenitor of violence, highlighting the interplay between religious rituals and political violence. The findings suggest that sacrificial violence, far from being a mere metaphor, plays a critical role in the construction and legitimization of collective violence in revolutionary contexts.